The globalisation of charismatic Christianity : spreading the gospel of prosperity - Coleman, Simon (Cambridge studies in ideology and religion, 2000)
This book is about conservative Protestant Christians and their spread around the globe. It focuses on "Health and Wealth" Christians. A ministry in Scandinavia is shown to be closely linked to evangelicals in other parts of the world, particularly the United States. The book provides the first extended account by an anthropologist of a Health and Wealth ministry. It makes a major contribution to an understanding of the material lives of these Christians: their art, architecture and uses of electronic technologies such as television, videos and the Internet.